Investigating hormone-induced changes in affective state using the affective bias test in male and female rats. (May 2020) - Hinchcliffe, Justyna K.; Mendl, Michael; Robinson, Emma S.J.
Highlights: The affective bias test provides new insights into the relationship between mood-related hormones and affective biases in rats. Treatment with oestradiol, bisphenol A and carbetocin induced significant positive affective biases in both male and female rats, whilst desmopressin induced a positive affective bias in males only. The opposite effects to oestradiol were found following formestane treatment, inducing a negative affective bias in both sexes. In male rats, a negative affective bias was developed following treatment with the low dose of progesterone, whilst in females following the higher dose of progesterone. Testosterone induced a dose-dependent negative affective bias in males, whilst in females there was no effect found. A positive affective bias was developed in both groups following treatment with the high dose of flutamide. Abstract: Recent clinical and pre-clinical research suggests that affective biases may play an important role in the development and perpetuation of mood disorders. Studies in animals have also revealed that similar neuropsychological processes can be measured in non-human species using behavioural assays designed to measure biases in learning and memory or decision-making. Given the proposed links between hormones and mood, we used the affective bias test to investigate the effects of different hormone treatments in both male and female rats. Animals were pre-treated with acute doses of hormone or vehicle control prior to learning each of two independent substrate-reward associations. During a subsequent choice test, positive or negative biases were observed by animal's preference towards or away from the substrate learnt during drug treatment respectively. In both sexes, oestradiol and the oestrogen-like compound bisphenol A induced positive biases, whilst blockade of oestrogen hormones with formestane induced a negative bias. Progesterone induced a negative bias in both sexes, but testosterone only induced a negative bias in males. Blocking testosterone with flutamide induced a positive bias in both sexes at the higher dose (10 mg/kg). The oxytocin analogue, carbetocin induced positive biases in both sexes but the vasopressin analogue, desmopressin, induced a positive bias in male rats only. These results provide evidence that modulating levels of hormones using exogenous treatments can induce affective biases in rats. They also suggest that hormone-induced affective biases influence cognitive and emotional behaviour and could have longer-term effects in some mood disorders.